Shattered midnight - Clayton, Dhonielle (Mirror (Hyperion (Publisher)), 2021)
In 1920s New Orleans, eighteen-year-old Zora, banished after an incident in Harlem, struggles with her overbearing family, magical powers, love of jazz, and forbidden romance with a white man.